The Influence Of Communication, Motivation, Work Environment On Employee Morale At Pt Indako Trading Coy - Solin, Yoshua Andre T; Sanny, Annisa (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
When improving employee performance, optimal competence is essential. Work enthusiasm plays a dominant role because usually Work enthusiasm is directly related to the basic abilities of individuals in carrying out a job. This study aims to determine the effect of communication, motivation, work environment on employee work enthusiasm at PT Indako Trading Coy. This study uses a quantitative approach with a survey method. In this study, the population was 37 employees of PT Indako Trading Coy, Makmur Branch. Based on the results obtained above, it can be seen that the coefficient of determination (R2) value is 0.791 or 79.1%. Thus, this value means that the variables of communication, motivation, work environment contribute an influence of 15.8% on work enthusiasm while the remaining 20.9% is influenced by other variables not discussed in this study.